Optimality criteria for human running investigated by forward dynamics simulations - Miller, R. H.; Umberger, B. R.; Caldwellaa, G. E. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
There are currently no generally accepted optimality criteria for human running. The purpose of the study was to test a set of potential criteria by generating performance based forward dynamics simulations. Simulation results were compared to measurements from human runners. Minimizing muscle activation generated the simulation that most accurately matched the experimental kinematic and metabolic data. The results suggest that minimizing activation, which avoids fatiguing any one muscle, is an important control policy for human running.